4D surface seismic tracks small supercritical CO2 injection into the subsurface: CO2CRC Otway Project. (August 2017) - Pevzner, Roman; Urosevic, Milovan; Popik, Dmitry; Shulakova, Valeriya; Tertyshnikov, Konstantin; Caspari, Eva; Correa, Julia; Dance, Tess; Kepic, Anton; Glubokovskikh, Stanislav; Ziramov, Sasha; Gurevich, Boris; et al.
Highlights: Cheaper and less intrusive seismic monitor surveys due to buried receiver spread. Buried geophone array substantially improves repeatability of 4D seismic. Seismic tracks small (∼10 kt) amount of CO2 injected into a geologic formation. Seismic can detect any CO2 leakages that compromise CO2 geosequestration projects. Abstract: Time-lapse (4D) seismic monitoring of injected CO2 in geological formations is being increasingly employed as the principal method for ensuring containment of the CO2 and testing conformance of predicted plume behaviour. However, to bring further confidence in this method, the CO2 volume detection limit in the seismic monitoring and key factors controlling it need to be quantitatively understood. The CO2CRC Otway Project attempts to improve this understanding by exploring the capability of seismic reflection method to detect and monitor a 15, 000 t injection of supercritical CO2 /CH4 mixture in a saline aquifer at a depth of 1500 m. To increase the signal to noise ratio and to reduce the disruption to land users, seismic acquisition is performed using a buried geophone array. Seismic acquisition occurred at injection intervals of 5000, 10, 000 and 15, 000 t over a 5-month period. The seismic images clearly show the distribution and evolution of the stored CO2 /CH4 plume. The analysis confirms that signal from pure CO2 would be of similar magnitude to the signal from CO2 /CH4 mixture. The results demonstrate the potential of time-lapse reflection seismic to provide key information to both operators and regulators for confirming the security and behaviour of stored CO2 at very small volumes.